Bupropion and naltrexone for smoking cessation: A double‐blind randomized placebo‐controlled clinical trial. Issue 4 (20th June 2016) - Mooney, ME; Schmitz, JM; Allen, S; Grabowski, J; Pentel, P; Oliver, A; Hatsukami, DK
Abstract : Combination of non‐nicotine pharmacotherapies has been underexamined for cigarette smoking cessation. A randomized, double‐blind, parallel‐group double‐dummy study evaluated two medications, bupropion (BUP) and naltrexone (NTX), in treatment‐seeking cigarette smokers ( N = 121) over a 7‐week treatment intervention with 6‐month follow‐up. Smokers were randomized to either BUP (300 mg/day) + placebo (PBO) or BUP (300 mg/day) + NTX (50 mg/day). The primary outcome was biochemically verified (saliva cotinine, carbon monoxide) 7‐day, point‐prevalence abstinence. BUP + NTX was associated with significantly higher point‐prevalence abstinence rates after 7‐weeks of treatment (BUP + NTX, 54.1%; BUP + PBO, 33.3%), P = 0.0210, but not at 6‐month follow‐up (BUP + NTX, 27.9%; BUP + PBO, 15.0%), P = 0.09. Continuous abstinence rates did not differ, P = 0.0740 (BUP + NTX, 26.2%; BUP + PBO, 13.3%). Those receiving BUP + NTX reported reduced nicotine withdrawal, P = 0.0364. The BUP + NTX combination was associated with elevated rates of some side effects, but with no significant difference in retention between the groups.